Almost periodic solutions of $N$-th order neutral differential difference equations with piecewise constant arguments - Rong-Kun Zhuang (Electronic Journal of Qualitative Theory of Differential Equations, 2013)
In this paper, we study the existence of almost periodic solutions of neutral differential difference equations with piecewise constant arguments via difference equation methods.